Expression and Predictive Value of Serum NLR, PLR Combined with SAA in Patients with Different Stages of Colorectal Cancer - Yang, Qinghua; Sun, Chengcheng; Zhao, Lisha (Frontiers in Surgery, 2022)
Colorectal cancer (CRC) is one of the major causes of death in the world, and has become a serious threat to human life. The prognosis of CRC patients in different pathological stages is quite different, so it is necessary to evaluate the clinical stages of CRC patients before operation. Neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), serum amyloid A (SAA) and other indicators have been widely proved to play the role of early diagnosis and prognosis monitoring in chronic inflammatory diseases and cancers. In this study, we collected clinical data of 103 patients with CRC confirmed by pathology in our hospital from January 2019 to December 2021. In addition, it aims to explore the expression and predictive value of NLR, PLR combined with SAA in patients with different stages of CRC, so as to provide reference for patients to choose a reasonable treatment plan. The results show that serum NLR, PLR combined with SAA can predict CRC staging effectively, which has certain auxiliary value for clinical decision-making.